More Sex-Determination Mutants of CAENORHABDITIS ELEGANS - Hodgkin, Jonathan (1980)
Sex determination in Caenorhabditis elegans is controlled by the X chromosome: autosome ratio, i.e. 2A;XX animals are hermaphrodite, and 2A;XO animals are male. A procedure for isolating 2A;XO animals that are transformed into hermaphrodites has been developed. Nine mutations causing this transformation have been obtained: eight are recessive, and all of these fall into a new autosomal complementation group, her-1 V. The remaining mutation (her-2) is dominant and has a genetic map location similar to that of tra-1 III. Recessive mutations of tra-1 cause the reverse transformation, transforming 2A;XX animals into males. Therefore, the her-2 mutation may result in constitutive expression of tra-1. Mutations in her-1 are without effect on XX animals, but the her-2 mutation prevents sperm production in both XX and XO animals, in addition to its effect on the sexual phenotype of XO animals. The epistatic relationships between tra and her genes are used to deduce a model for the action of these genes in controlling sex determination.